Pengaruh Penerapan Pendekatan Deep Learning Berbantuan Media Congklak Terhadap Hasil Belajar Siswa Kelas III Materi Perkalian Di SDN Kranjingan 03 - Susanto; A'izzatul Khumairoh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In Indonesia, the mathematics learning process tends to apply abstract concepts, directing students to memorize rather than understand, and is considered a difficult and unpleasant subject. The lack of contextualization in learning often results in students being taught without the use of concrete media or media related to real-life experiences. One alternative that can be used is to apply a deep learning approach assisted by congklak media. This study aims to examine the significant effect of applying a deep learning approach assisted by congklak media on the learning outcomes of third-grade students in multiplication at SDN Kranjingan 03. This study used a pre-experimental pattern, namely a One Group Pretest-Posttest design. The subjects of this study were all third-grade students at SDN Kranjingan 03, consisting of 28 students. The data were analyzed using normality tests and pairedt samples tests. The results showed that there was a significant effect of the application of the deep learning approach assisted by the congklak media on the learning outcomes of third-grade students in multiplication at SDN Kranjingan 03. This was proven by the results of the hypothesis test using the Paired Samples Test, with the result that the t-count value was -11.811 with a t-table value at df = 27 with a significance level of 5% being 2.052. This shows that the t-count value is ≥ t-table. In addition, the significance value (sig. 2 tailed) reached 0.000 < 0.05. Thus, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted.